Análisis del anticipo al impuesto a la renta dentro de los ingresos permanentes del Presupuesto General del Estado de Ecuador - Mora Potes, Larry Cliff (2022)
The next analysis of the Income Tax Advance within the permanent incomes of the General State Budge of Ecuador is to evalue the behavior of the Income Tax Advance as apermanent state income in the study period 2015-2020. Under national regulations and, coupled with the different reforms, this work will be developed with a mixed approach, through the processing and analysis of data obtained from the platform of the Internal Revenue Service and the Ministry of Finance of Ecuador........